2019
DOI: 10.1007/s40261-019-00834-0
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Sildenafil in Preterm Infants at Risk of Bronchopulmonary Dysplasia: A Pilot Randomized, Double-Blinded, Placebo-Controlled Trial

Abstract: Background Bronchopulmonary dysplasia (BPD) is the need for oxygen therapy at 36 weeks postmenstrual age (PMA). Sildenafil has been shown to enhance the lung alveolarization and vascularization in newborn animal models after lung injury and has possible therapeutic potential for the prevention of BPD. Objective To perform a proof-of-concept, Phase II, pilot randomized, double-blind, clinical trial to study the efficacy of sildenafil in preventing BPD, in postnatal (< 24 h), extremely and very preterm infants. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Systematic review shows that in the treatment of BPD-associated pulmonary hypertension in preterm infants, sildenafil may be associated with improvement in pulmonary artery pressure and respiratory scores. 38 Abounahia et al 39 found oral sildenafil did not benefits in the prevention of BPD or death in the extreme and very preterm infants. A retrospective series of 25 patients with BPD aged <2 years showed hemodynamic improvement in pulmonary hypertension in majority cases, with minimal adverse events.…”
Section: Is Sildenafil Effective In Bpd Associated Pulmonary Hypertenmentioning
confidence: 98%
“…Systematic review shows that in the treatment of BPD-associated pulmonary hypertension in preterm infants, sildenafil may be associated with improvement in pulmonary artery pressure and respiratory scores. 38 Abounahia et al 39 found oral sildenafil did not benefits in the prevention of BPD or death in the extreme and very preterm infants. A retrospective series of 25 patients with BPD aged <2 years showed hemodynamic improvement in pulmonary hypertension in majority cases, with minimal adverse events.…”
Section: Is Sildenafil Effective In Bpd Associated Pulmonary Hypertenmentioning
confidence: 98%
“…Prophylactic sildenafil in neonatal rats exposed to hyperoxia has been shown to improve alveolarization, promote angiogenesis, decrease lung inflammation and fibrin deposition, and thus decrease BPD via activation of hypoxia-inducible factor signaling pathway (208)(209)(210). However, RCTs studying the effect of prophylactic sildenafil in preterm infants did not demonstrate any significant impact on BPD or death (211,212).…”
Section: Sildenafilmentioning
confidence: 99%
“…especially for infants whose hip joints are mainly cartilage, therefore the results of hip ultrasound examination are more reliable (9). Ultrasound Graf method can be used to evaluate development of the hip joint by analyzing the ultrasound images of the hip joint and quantifying the shape of the acetabulum with α and β angles (10). The results of this study showed that there was a significant difference in α and β angles between the cases with congenital acetabular dysplasia and those with normal hip joints by ultrasound Graf method, which is consistent with the reports of Fooladi (11), suggesting that the ultrasound Graf method can be used as one of the methods to screen congenital acetabular abnormalities, with strong operability and high standardization.…”
Section: Congenital Hip Dysplasia Is a Common Limb Deformity Inmentioning
confidence: 99%